Remote Control of Mobile Robot using the Virtual Reality - Ibari Benaoumeur; Ahmed-Foitih Zoubir; Haniﬁ Elhachimi Amar Reda (Institute of Advanced Engineering and Science, 2015)
In this paper we present the simulation and manipulation of teleoperation system for remote control of mobile robot using the Virtual Reality (VR). The objective of this work is to allow the operator to control and supervise a unicycle type mobile robot. In this research we followed three ways: The use of articulated robotic mobile on the Web, the design of remote environment for the experimentation using the network for the mobile robot and the architecture of control is proposed to facilitate the piloting of the robot. This work proposes a hardware and software architecture based on communication and information technologies to control the virtual robot to improve the control towards the remote robot. A path planning method is integrated to the remote control system. Results show the real possibilities offered by this manipulation, in order to follow a trajectory of the robot and to create applications with a distance access to facilities through networks like the Internet and wireless.